VEGF Axonal Transport Dependent on Kinesin-1B and Microtubules Dynamics - Yang, Ping; Sun, Xiao; Kou, Zeng-Wei; Wu, Kun-Wei; Huang, Ya-Lin; Sun, Feng-Yan (Frontiers in Molecular Neuroscience, 2017)
Axon-transport plays an important role in neuronal activity and survival. Reduced endogenous VEGF can cause neuronal damage and axon degeneration. It is unknown at this time if VEGF can be transported within the axon or whether it can be released by axonal depolarization. We transfected VEGF-eGFP plasmids in cultured hippocampal neurons and tracked their movement in the axons by live-cell confocal imaging. Then, we co-transfected phVEGF-eGFP and kinesin-1B-DsRed vectors into neurons and combined with immunoprecipitation and two-color imaging to study the mechanism of VEGF axon-trafficking. We found that VEGF vesicles morphologically co-localized and biochemically bounded with kinesin-1B, as well as co-trafficked with it in the axons. Moreover, the capacity for axonal trafficking of VEGF was reduced by administration of nocodazole, an inhibitor of microtubules, or kinesin-1B shRNA. In addition, we found that VEGF could release from the cultured neurons under acute depolarizing stimulation with potassium chloride. Therefore, present findings suggest that neuronal VEGF is stored in the vesicles, actively released, and transported in the axons, which depends on the presence of kinesin-1B and functional microtubules. These results further help us to understand the importance of neuronal VEGF in the maintenance of neuronal activity and survival throughout life.